Avaliação da política pública penitenciária no Ceará: um recorte analítico contemporâneo das vivências laborais de policiais penais - Albuquerque Junior, Ailton Batista de (2021)
This dissertation, called Evaluation of the Penitentiary Public Policy in Ceará: an analytical-contemporary approach of the working experiences of Penal Police Officers, has as its general objective, to know the Penitentiary Public Policy in Brazil, deepening in the context of Ceará, through interviews with Penal Police Officers, having as specific objectives to unveil the design and configurations that led to the course of this academic-scientific study, outlining the evaluative perspective, the ethical-political procedures and the place of speech of the researcher as a demanding of this endeavor; to outline the concept of evaluation of public policies and the characterization of the object of study, through balances, from the origin of the penalty and its socio-historical vicissitudes to the realization of succinct weavings for the configurations and development of the Brazilian penitentiary system; To deduce the Penitentiary Policy in Brazil, based on its text, context, and legal landmarks, through the material, legal, educational, social, religious and health assistance and to evaluate the penitentiary public policy of Ceará, analyzing the context of creation and extinction of penal units, unveiling the rancor and advances in prison education and listing the work as a right to prisoner in sui generis conjuncture. The academic-scientific course and its configurations occurred through a qualitative approach based on the historical-dialectical materialism, considering theory, method, and creativity. Therefore, we resorted to a descriptive and exploratory research during 6 months (February to July 2021), applied via Whatsapp, due to the context of social isolation to contain the covid-19 pandemic. As for the technical procedures, we used the bibliographic research that is a prerequisite for any other modalities and the documental research, through news on the internet and national, international and local legislations, evaluating the penitentiary policy of Ceará, questioning penal police officers, through a semi-structured script about the exercise of their functions inherent to people in situation of provisional or sentenced deprivation of liberty. Therefore, the methodological perspective of the evaluation of this public policy is grounded on the experiential model (LEJANO, 2012), being the data tabulated through content analysis (BARDIN, 2011). The final considerations of this study discuss that the prison policy in Ceará has structures with social, medical, legal, legal and psychological assistance only in reserves that make up the reference penal units. However, there is a lack of projects with greater financial application regarding the professional qualification of prisoners and lack of work for the remission of the sentence of the convicts.